(untitled) (Archives of Clinical and Medical Case Reports, 2018)
A 83 years old man was operated due to the acute abdominal findings and left strangulated inguinal hernia. On the exploration, trapping of sigmoid colon in the left inguinal canal observed and colonic wall was partly necrotic. After reduction, when the peritoneum covering the mesentery of the colon was opened, posterior wall defect and colonic content was seen in the mesentery. This view explained the CT that shows free air without free fluid in the abdomen. End Colostomy with Hartmann’s Pouch was the choice of the operation.